2022
DOI: 10.1371/journal.pone.0267939
|View full text |Cite|
|
Sign up to set email alerts
|

Silicon fertilization counteracts salinity-induced damages associated with changes in physio-biochemical modulations in spinach

Abstract: Plant growth and productivity are limited by the severe impact of salt stress on the fundamental physiological processes. Silicon (Si) supplementation is one of the promising techniques to improve the resilience of plants under salt stress. This study deals with the response of exogenous Si applications (0, 2, 4, and 6 mM) on growth, gaseous exchange, ion homeostasis and antioxidant enzyme activities in spinach grown under saline conditions (150 mM NaCl). Salinity stress markedly reduced the growth, physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…In the present study, enhanced proline content was observed under heat stress compared with control temperatures. Increased accumulation of proline due to heat stress has been reported by other researchers, who concluded that proline helps to stabilise membranes, subcellular structures and cellular redox potential by destroying the radicals (Hussain et al 2018;Wang et al 2018;Naz et al 2022). Liu et al (2011) observed a significant increase in starch content under heat-shock treatment >30°C.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In the present study, enhanced proline content was observed under heat stress compared with control temperatures. Increased accumulation of proline due to heat stress has been reported by other researchers, who concluded that proline helps to stabilise membranes, subcellular structures and cellular redox potential by destroying the radicals (Hussain et al 2018;Wang et al 2018;Naz et al 2022). Liu et al (2011) observed a significant increase in starch content under heat-shock treatment >30°C.…”
Section: Discussionsupporting
confidence: 53%
“…The application of Si alleviated heat stress significantly by improving the water status of spinach plants. Naz et al (2022) found that, at a balanced Si concentration, RWC was almost constant under abiotic stress, which was probably due to an advanced ability for osmotic adjustment. Moreover, Si application helps in removing restrictions and improves turgor pressure in the cells to maintain water balance.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%